Strategi Strategi Peningkatan Pelayanan Melalui Sistem Informasi Administrasi Di Kelurahan Komering Agung - Yuyun Fitriani; Wiska Rima Jaya (Bahasa Indonesia, 2023)
The implementation of public services must pay attention to several aspects, including fast in implementation, efficient in the use of human resources, effective in time execution, and transparent to the public. Good and quality services have implications for community satisfaction, because the public directly evaluates the performance of the services provided. The indicator of community satisfaction is the benchmark for the success of governance. In order to provide more efficient and effective public services, the government has begun to adapt to technological sophistication, namely by using information systems or applications in providing services to the public. The purpose of this research is to find out how administrative services in Komering Agung Village are after the implementation of website-based population administration services. The research method used is a qualitative method with the process of collecting data using interview techniques, observation and documentation. The research results obtained are that the service improvement strategy through the administrative information system in the Komering Agung Village is going well because the community as service recipients feels the good impact of services through the website where services are more efficient in terms of time and costs.